Thrombolytic Treatment with Tissue-type Plasminogen Activator (t-PA) Containing Liposomes in Rabbits: a Comparison with Free t-PA - Heeremans, J L M; Prevost, R; Bekkers, M E A; Los, P; Emeis, J J; Kluft, C; Crommelin, D J A (Thrombosis and Haemostasis, 1995)
In this study, we aimed at improving the therapeutic index of tissue- type Plasminogen Activator (t-PA) as thrombolytic agent in the treatment of myocardial infarction. Liposome-encapsulated t-PA was tested in a rabbit jugular vein thrombosis model: administration of free t-PA (t-PA) as a bolus injection in the ear vein was compared to a similar administration of liposomal t-PA (t-PA-lip), liposomal t-PA in plasminogen-coated liposomes (Plg-t-PA-lip), a mixture of free t-PA and empty liposomes (t-PA+empty lip) and a saline-blank (blank) in terms of thrombolytic activity and side effects.Liposomal t-PA (t-PA-lip/Plg-t-PA-lip) showed a significantly better thrombolysis efficiency than equimolar doses of free t-PA (t-PA/ t-PA+ empty lip): about 0.24 mg/kg of liposomal t-PA practically equalled the lysis-activity of a dose of free t-PA of 1.0 mg/kg (t-PAlmg/kg). On the other hand, liposome encapsulation did not affect the systemic activation of alpha2-antiplasmin and plasminogen by t-PA.We conclude that for this model an improvement in thrombolytic efficacy of t-PA is achieved by liposome encapsulation of t-PA. As t-PA-lip and Plg-t-PA-lip -treatment induced similar results, targeting of liposomal t-PA by coupled glu-Plg remains a topic to be optimized in future studies.